Electromigration-induced resistance switching in indented Al microstrips. (12th November 2019) - Lombardo, J; Collienne, S; Petrillo, A; Fourneau, E; Nguyen, N D; Silhanek, A V
Abstract: Non-volatile resistive memory cells are promising candidates to tremendously impact the further development of Boolean and neuromorphic computing. In particular, nanoscale memory-bit cells based on electromigration (EM)-induced resistive switching in monolithic metallic structures have been identified as an appealing and competitive alternative to achieve ultrahigh density while keeping straightforward manufacturing processes. In this work, we investigate the EM-induced resistance switching in indented Al microstrips. In order to guarantee a large switching endurance, we limited the on-to-off ratio to a minimum readable value. Two switching protocols were tested, (i) a variable current pulse amplitude adjusted to ensure a precise change of resistance, and (ii) a fixed current pulse amplitude. Both approaches exhibit an initial training period where the mean value of the device's resistance drifts in time, followed by a more stable behavior. Electron microscopy imaging of the devices show irreversible changes of the material properties from the early stages of the switching process. High and low resistance states show retention times of days and endurances of ∼10 3 switching cycles.